UHPC (Ultra High Performance Concrete) based on carbon nanotube modified aggregate as well as preparation method and application of UHPC
By using carboxy-functionalized carbon nanotubes to modify sintered armor alumina aggregate, the problem of the platform effect of ultra-high performance concrete anti-invasion performance is solved, and stronger anti-invasion performance and improved microstructure are achieved.
Patent Information
- Application Number
- CN202510088277.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-02-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Ultra-high performance concrete has a platform effect in terms of intrusion resistance, and the transition zone between the aggregate-matrix interface is weak, limiting the further improvement of intrusion resistance.
Carboxy-functionalized carbon nanotubes are used to modify the sintered bauxite aggregate, and chemical reactions with the hydrated calcium silicate and Ca(OH)2 in the cement matrix through the carboxy-functionalized carbon nanotubes, forming stronger covalent bonds, improving the microstructure of the cement matrix and enhancing its anti-invasion performance.
Through the use of modified aggregates, the anti-invasion performance of concrete is significantly improved, the strength and load transfer efficiency of cement matrix are enhanced, and the crack expansion and stress concentration are reduced.
Smart Images

Figure CN119528523A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of new building materials, and in particular relates to a UHPC based on carbon nanotube modified aggregate and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Ultra-High Performance Concrete (UHPC) is a new type of cement-based composite material with ultra-high strength, high toughness and high durability. Compared with ordinary concrete, ultra-high performance concrete has significant advantages in terms of penetration and explosion resistance. For example, under the same penetration conditions, its penetration depth and pit damage are much smaller than ordinary concrete. However, after the strength of ultra-high performance concrete is increased to a certain threshold, its higher compressive strength cannot be effectively converted into penetration resistance, that is, there is a platform effect.
[0004] The anti-penetration bottleneck of UHPC can be attributed to the following aspects. Although aggregates improve the anti-penetration performance of UHPC to a certain extent, the addition of aggregates also introduces a relatively weak aggregate-matrix interface transition zone, which limits the further improvement of anti-penetration performance. The main hydration product of the UHPC matrix is calcium silicate hydrate gel (CSH). About 1 / 3 of the calcium silicate hydrate gel is connected by weak van der Waals force, which can be invalidated with very low energy. In addition, the material expands or contracts during the formation of CSH gel. This volume change will produce stress concentration when restricted by other components of the matrix, leading to the formation of microcracks, thereby limiting the anti-penetration ability of the UHPC matrix. In recent years, high-strength and high-hardness coarse aggregates (such as sintered bauxite coarse aggregates) have been successfully introduced into UHPC to improve its anti-penetration performance, especially the penetration depth. However, due to the limitations of van der Waals forces and microcracks in the pores of the material, the penetration resistance of the ultra-high performance concrete matrix is still difficult to effectively improve, which limits the promotion and application of ultra-high performance concrete in protective engineering. Summary of the invention
[0005] In order to overcome the deficiencies of the prior art, the purpose of the present invention is to provide a UHPC based on carbon nanotube modified aggregate and a preparation method and application thereof, and to modify the ultra-high performance concrete matrix by using graphene oxide to improve its anti-penetration performance under the action of high-speed projectiles.
[0006] In order to achieve the above object, the technical solution of the present invention is: In a first aspect, the present invention provides a UHPC based on carboxyl functionalized carbon nanotube modified aggregate, which is prepared from raw materials comprising the following components in parts by weight: 1417-1517 parts of cement, 135-165 parts of silica fume, 35-43 parts of steel fiber, 800-1000 parts of sintered bauxite aggregate, 4.22-10.56 parts of carboxyl functionalized carbon nanotubes, 410-510 parts of water and 6-12 parts of water reducer; Among them, the sintered bauxite aggregate is modified by carboxyl-functionalized carbon nanotubes.
[0007] In a second aspect, the present invention provides a method for preparing the above-mentioned UHPC based on carbon nanotube modified aggregate, comprising the following steps: S1, preparing a carboxyl functionalized carbon nanotube dispersion and modifying sintered bauxite aggregate; S2, mixing cement, silica fume and water to obtain a first mixture; S3, mixing the first mixture with steel fibers to obtain a second mixture; S4. Adding the modified sintered bauxite aggregate to the second mixture, mixing and stirring to obtain the UHPC based on the carboxyl functionalized carbon nanotube modified aggregate.
[0008] In a third aspect, the present invention provides the application of the above-mentioned UHPC based on carbon nanotube modified aggregate in protective engineering.
[0009] The beneficial effects of the present invention are: 1. The present invention improves the mechanical properties and anti-penetration performance of concrete by compounding multiple materials. Specifically, the hydrophilicity of the oxygen-containing functional groups (carboxyl groups) in the carboxyl-functionalized carbon nanotubes is used to react chemically with the calcium silicate hydrate (CSH) and Ca(OH)2 in the cement, replacing the originally weak van der Waals force in CSH to form a stronger covalent bond, catalyzing and promoting the hydration reaction in the cement. In addition, the carboxyl-functionalized carbon nanotubes have good dispersibility, which not only helps the carboxyl-functionalized carbon nanotubes to provide more nucleation sites and promote the generation of more hydration products in the cement matrix, but also can simultaneously connect the hydration products CSH and Ca(OH)2, so that CSH and Ca(OH)2 are connected as a whole through the carboxyl-functionalized carbon nanotubes, thereby enhancing the strength of the cement-based matrix and improving the load transfer efficiency between the cement matrix and the carboxyl-functionalized carbon nanotubes. The CSH gel generated at the same time can play a role in filling pores and gaps, improving the microstructure of cement-based materials, and further improving their integrity.
[0010] 2. The present invention first uses carboxyl functionalized carbon nanotubes to modify the aggregate. Based on the unique structure of large aspect ratio, carboxyl functionalized carbon nanotubes can be combined, embedded and bridged with cement-based materials to connect different components in the cement matrix. When the cement-based material is subjected to external load, the carboxyl functionalized carbon nanotubes can inhibit the generation and development of micro cracks between the aggregate and the concrete matrix at the nanoscale, inhibit the generation and development of cracks in the cement matrix at the nanoscale, and achieve effective matrix reinforcement. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0012] Figure 1 It is a schematic diagram of the principle of a specific implementation mode of the present invention.
[0013] Figure 2 It is a schematic diagram of the action mode of carboxyl functionalized carbon nanotubes in a cement matrix according to a specific embodiment of the present invention.
[0014] Figure 3 It is a statistical diagram of the static mechanical properties of concrete materials prepared in the examples and comparative examples in the specific implementation manner of the present invention.
[0015] Figure 4 It is a statistical diagram of the anti-penetration performance of concrete materials prepared in examples and comparative examples in a specific implementation manner of the present invention. DETAILED DESCRIPTION
[0016] A typical embodiment of the present invention provides a UHPC based on carbon nanotube modified aggregate, which is prepared from raw materials including the following components in parts by weight: 517-617 parts of cement, 135-165 parts of silica fume, 35-43 parts of steel fiber, 800-1000 parts of sintered bauxite aggregate, 4.22-10.56 parts of carboxyl functionalized carbon nanotubes, 410-510 parts of water and 6-12 parts of water reducing agent; Among them, the sintered bauxite aggregate is modified by carboxyl-functionalized carbon nanotubes.
[0017] like Figure 1 As shown, carboxyl functionalized carbon nanotubes have a high aspect ratio, with a tube diameter of 0.4-100nm and a length of 0.1-100μm. The aspect ratio of carboxyl functionalized carbon nanotubes is generally around 1000, and can reach 10 in special cases. 7; The content of carboxyl functional groups in every 100nm length range is ≥3, with good dispersibility and stability; The hydrophilicity of the oxygen-containing functional groups (carboxyl) in carboxyl-functionalized carbon nanotubes is used to react chemically with calcium silicate hydrate (CSH) and Ca(OH)2 in cement, replacing the originally weak van der Waals force in CSH to form a stronger covalent bond, catalyzing and promoting the hydration reaction in cement. Carboxyl-functionalized carbon nanotubes have good dispersibility, which not only helps carboxyl-functionalized carbon nanotubes provide more nucleation sites and promote the production of more hydration products in the cement matrix, but also enables CSH and Ca(OH)2 to be connected as a whole through carboxyl-functionalized carbon nanotubes, thereby enhancing the strength of the cement-based matrix and improving the load transfer efficiency between the cement matrix and the carboxyl-functionalized carbon nanotubes, so that the generated CSH gel can fill pores and gaps, improve the microstructure of cement-based materials, and further improve its integrity.
[0018] Optionally, the maximum particle size of the sintered bauxite aggregate is 10 mm, the aggregate crushing index is 8.0%, the elastic modulus is 240 GPa, and the density is 3.2 g / cm 3 ; The sintered bauxite is modified by carboxyl functionalized carbon nanotubes, and a uniform carbon nanotube coating or composite is formed on the surface of the modified sintered bauxite, showing obvious surface roughening and structural strengthening phenomena. The carboxyl (-COOH) functional groups of the carbon nanotubes interact with the surface of the bauxite, and may form hydrogen bonds, electrostatic attraction or partial chemical bonding, thereby enhancing the bonding force and compatibility between the sintered bauxite and the cement matrix. The dispersibility, compressive strength and crack resistance of the modified sintered bauxite in cement-based materials are improved. The addition of carboxyl functionalized carbon nanotubes can improve the microstructure of sintered bauxite, enhance its dispersibility and interfacial compatibility in concrete, and further enhance its reinforcing effect on the cement matrix, thereby improving the rheology of cement paste, improving the density of concrete, and enhancing mechanical strength and anti-penetration performance.
[0019] Optionally, the cement is 52.5 grade or 52.5R grade Portland cement or ordinary Portland cement.
[0020] Optionally, the content of amorphous silicon dioxide in the silica ash is greater than 95 wt %, and the specific surface area of the silica ash is greater than 21.0 m 2 / g, and its specific density is greater than 2.2; the silica fume used in the present invention is an ultra-fine dry powder that has not been completely densified.
[0021] Optionally, the steel fiber is a copper-plated straight steel fiber with an average length of 13 mm and an average diameter of 0.16 mm, a tensile strength greater than 2500 MPa, an elastic modulus of 200 GPa, and a density of 7800 kg / m 3 .
[0022] Optionally, the carboxyl functionalized carbon nanotubes are one or more of multi-walled carboxyl functionalized carbon nanotubes and single-walled carboxyl functionalized carbon nanotubes, wherein multi-walled carbon nanotubes have multiple coaxial carbon tube layers, generally have higher mechanical strength and temperature resistance, and are suitable for applications requiring stronger reinforcement effects; while single-walled carbon nanotubes have higher electrical conductivity and smaller diameter, and are suitable for materials requiring higher electrical properties. Both are treated with carboxyl functionalization to enhance compatibility with other materials, provide better dispersibility and stability, and the appropriate type can be selected according to specific application requirements.
[0023] A typical embodiment of the present invention provides a method for preparing the above-mentioned UHPC based on carbon nanotube modified aggregate, comprising the following steps: S1, preparing a carboxyl functionalized carbon nanotube dispersion and modifying sintered bauxite aggregate; S2, after mixing cement and silica fume, adding water reducer and water and continuing to mix and stir to obtain a first mixture; S3, mixing the first mixture with steel fibers to obtain a second mixture; S4. Adding the modified sintered bauxite aggregate to the second mixture, mixing and stirring to obtain the UHPC based on the carboxyl functionalized carbon nanotube modified aggregate.
[0024] Optionally, in S1, the aggregate modification method is a physical adsorption method or a chemical modification method.
[0025] The physical adsorption method includes: uniformly coating or impregnating the carboxyl functionalized carbon nanotube dispersion on the aggregate surface, using physical adsorption to make the carbon nanotubes adhere to the aggregate surface to form a modified layer; or, using ultrasonic treatment to uniformly disperse the carbon nanotubes in the liquid phase, and then spraying or impregnating it onto the aggregate surface to enhance the dispersibility and modify the aggregate.
[0026] The chemical modification method includes: mixing the carboxyl functionalized carbon nanotube dispersion with aggregate and then heat treating and drying it, so that the carbon nanotubes react chemically with the aggregate surface or form covalent bonds to form a modified layer, thereby enhancing the bonding force between the aggregate and the cement matrix; or, using a vapor deposition method to deposit the carboxyl functionalized carbon nanotubes on the aggregate surface under high temperature conditions to further enhance the modification effect.
[0027] Optionally, in S2, during the mixing process of cement and silica fume, stir at a speed of 75-85 rpm (low speed stirring) for 2-3 min; when the water reducer and water are added and continued to be mixed and stirred, stir at a speed of 75-85 rpm (low speed stirring) for 3-5 min. Low speed stirring can prevent powder splashing.
[0028] Optionally, in S3, after the freshly mixed concrete (ie, the first mixture) has good fluidity, the steel fibers are slowly added through a square hole sieve.
[0029] Optionally, in S3, the mixing is stirring mixing; the stirring mixing speed before adding the steel fiber is 155-165 rpm (medium speed stirring) and the time is 3-5 min; after adding the steel fiber, high-speed stirring (355-365 rpm) is performed for 1-2 min.
[0030] Optionally, in S4, the fresh concrete (i.e., the second mixture) is mixed with the modified aggregate, followed by two minutes of low-speed mixing (at a rotation speed of 75-85 rpm), and then immediately two minutes of high-speed mixing (at 355-365 rpm) to complete the mixing.
[0031] Optionally, the method further includes step S5, casting and curing to a specified age.
[0032] Optionally, use a vibrating table to vibrate lightly for 1-2 minutes during the pouring process to help expel bubbles and improve its density. After pouring, cover with plastic film to prevent surface moisture loss and demould after 24 hours.
[0033] Optionally, the curing is carried out under standard conditions (temperature 20±2°C, relative humidity>95%RH).
[0034] A typical embodiment of the present invention provides the application of the above-mentioned UHPC based on carbon nanotube modified aggregate in protective engineering.
[0035] Specifically, it includes applications in fortifications, missile launch sites, nuclear waste storage facilities, main structures of large-span bridges, and war-readiness highways.
[0036] like Figure 2As shown in the figure, carboxyl functionalized carbon nanotubes can combine with different components in cement-based materials, embed and form a bridge effect based on their unique structure with large aspect ratio, thereby effectively enhancing the overall performance of the cement matrix; when the cement-based material is subjected to external load, carboxyl functionalized carbon nanotubes can not only inhibit the generation and expansion of microcracks between aggregate and cement matrix at the nanoscale, but also effectively inhibit the formation and development of cracks inside the cement matrix; the role of modified aggregate is mainly reflected in the following aspects: first, the modified aggregate can significantly improve the interfacial adhesion between aggregate and cement matrix and enhance the mechanical properties of cement-based composites by combining with carboxyl functionalized carbon nanotubes; secondly, carbon nanotubes can form a nanoscale reinforcement network inside the material, effectively disperse the external load, thereby slowing down the expansion of cracks and improving the crack resistance. In addition, the modified aggregate can inhibit the expansion of microcracks in the cement matrix through the synergistic effect with carbon nanotubes, play a "self-healing" role, improve the durability, toughness and crack resistance of the composite material, and finally achieve matrix reinforcement and performance improvement of cement-based composites.
[0037] Preparation Example 1 A method for preparing a carboxyl functionalized carbon nanotube dispersion comprises: S11, mixing the dispersion liquid TNWDIS (commercially available carbon nanotube aqueous dispersant) and deionized water at a volume ratio of 1:10, stirring at a rotation speed of 400-600 rpm for 5-10 minutes until uniform, to obtain a mixed solution; S12: gradually adding a set mass fraction of carboxyl-functionalized carbon nanotubes to the mixed solution, stirring at a speed of 400-600 rpm for 10-15 min until the mixture is uniform, to obtain a mixed solution of carboxyl-functionalized carbon nanotubes; S13: The carboxyl functionalized carbon nanotube dispersion was ultrasonically treated with a 650W ultrasonic cell disruptor for 20-30 minutes, and the amplitude was set to 30% within a 4s period to obtain a carboxyl functionalized carbon nanotube dispersion. During the ultrasonic treatment, the amplitude was set to 30% with a 4s period. During the process, the cavitation effect of ultrasound and the strong micro-impacts generated by the continuous bursting of bubbles in the liquid helped to break up the agglomerates of carbon nanotubes, thereby achieving uniform dispersion. Setting the amplitude to 30% helped to avoid temperature increases caused by excessive amplitudes, thereby avoiding unnecessary thermal damage to the material. Controlling the time and amplitude of ultrasonic treatment can ensure that the carbon nanotubes maintain good dispersion in water, while avoiding unnecessary material degradation caused by excessive temperatures, thereby ensuring the structural stability and dispersion effect of the carbon nanotubes.
[0038] In this preparation example, carboxyl functionalized carbon nanotubes are commercially available products with specifications of tube diameter 0.4-100 nm, length 1-100 μm, purity ≥95%, and carboxyl functional group content ≥3 per 100 nm length range. It was detected that the elastic modulus of the carboxyl functionalized carbon nanotubes was as high as 1000 GPa, the tensile strength was between 100-200 GPa, and the ultimate strain was close to 12%.
[0039] Example 1 A UHPC based on carbon nanotube modified aggregate is prepared from raw materials including the following components in parts by weight: 567 parts of 52.5 grade ordinary Portland cement, 147 parts of incompletely densified silica fume, 4.22 parts of carboxyl functionalized carbon nanotubes, 39 parts of copper-plated straight steel fibers, 900 parts of sintered bauxite aggregate, 452 parts of tap water, and 5 parts of polycarboxylic acid-based high-efficiency water reducer; Among them, the sintered bauxite aggregate is modified by carboxyl-functionalized carbon nanotubes.
[0040] The carboxyl functionalized carbon nanotubes in this example are taken in 4.22 parts, which are obtained through multiple experiments and theoretical calculations.
[0041] The preparation method comprises: S1. Obtain a carboxyl-functionalized carbon nanotube dispersion according to the method of Preparation Example 1, mix the dispersion with sintered bauxite aggregate, and modify it by physical impregnation; specifically, immerse the sintered bauxite aggregate in the carboxyl-functionalized carbon nanotube dispersion, take it out after standing for a set time, and obtain the modified aggregate after sufficient drying.
[0042] S2. After mixing cement and silica fume, stir at a speed of 75 rpm (low-speed stirring) for 2 min. After adding the water reducing agent and water, continue stirring at a speed of 75 rpm (low-speed stirring) for 3 min to obtain a first mixture.
[0043] S3. Stir the freshly mixed concrete (i.e., the first mixture) at 155 rpm for 3 min until it has good fluidity, then slowly add steel fiber through a square hole sieve, and then stir at high speed (355 rpm) for 1 min to obtain a second mixture.
[0044] S4. Add modified aggregate to the second mixture, stir at 75 rpm for 2 min, and then immediately stir at 355 rpm for 2 min to complete the mixing.
[0045] S5. Pour the mixed concrete into shape. During the pouring process, use a vibrating table to lightly vibrate for 1 minute to expel bubbles. After pouring, cover with plastic film to prevent surface moisture loss and demould after 24 hours. Curing under standard conditions (temperature 20±2℃, relative humidity>95%RH) to the specified age.
[0046] Example 2 A UHPC based on carbon nanotube modified aggregate is prepared from raw materials including the following components in parts by weight: 567 parts of 52.5R grade ordinary Portland cement, 147 parts of incompletely densified silica fume, 6.33 parts of carboxyl functionalized carbon nanotubes, 39 parts of copper-plated straight steel fibers, 900 parts of sintered bauxite aggregate, 452 parts of tap water, and 6.5 parts of polycarboxylic acid-based high-efficiency water reducer; wherein the sintered bauxite aggregate is modified by carboxyl functionalized carbon nanotubes.
[0047] The preparation method is the same as that in Example 1.
[0048] Example 3 A UHPC based on carbon nanotube modified aggregate is prepared from raw materials including the following components in parts by weight: 567 parts of 52.5R grade ordinary Portland cement, 147 parts of incompletely densified silica fume, 8.44 parts of carboxyl functionalized carbon nanotubes, 39 parts of copper-plated straight steel fibers, 900 parts of sintered bauxite aggregate, 452 parts of tap water, and 6.5 parts of polycarboxylic acid-based high-efficiency water reducing agent; the sintered bauxite aggregate is modified by carboxyl functionalized carbon nanotubes.
[0049] The preparation method is the same as that in Example 1.
[0050] Example 4 A UHPC based on carbon nanotube modified aggregate is prepared from raw materials including the following components in parts by weight: 567 parts of 52.5 grade ordinary Portland cement, 147 parts of incompletely densified silica fume, 10.56 parts of carboxyl functionalized carbon nanotubes, 39 parts of copper-plated straight steel fibers, 900 parts of sintered bauxite aggregate modified by carboxyl functionalized carbon nanotubes, 452 parts of tap water, and 6.5 parts of polycarboxylic acid-based high-efficiency water reducer; wherein the sintered bauxite aggregate is modified by carboxyl functionalized carbon nanotubes.
[0051] The preparation method is the same as that in Example 1.
[0052] Comparative Example 1 A UHPC is prepared from raw materials including the following components in parts by weight: 567 parts of 52.5-grade ordinary Portland cement, 147 parts of incompletely densified silica fume, 39 parts of copper-plated straight steel fibers, 900 parts of sintered bauxite aggregate, 452 parts of tap water, and 6.5 parts of a polycarboxylic acid-based high-efficiency water reducer.
[0053] The preparation method is the same as steps S2, S3, S4 and S5 in Example 1.
[0054] The difference from Example 1 is that the aggregate is not modified by carboxyl-functionalized carbon nanotubes.
[0055] Comparative Example 2 A UHPC based on carbon nanotube modification is prepared from raw materials including the following components by weight: 1467 parts of 52.5 grade ordinary Portland cement, 147 parts of incompletely densified silica fume, 4.22 parts of carboxyl functionalized carbon nanotubes, 39 parts of copper-plated straight steel fibers, 452 parts of tap water, and 5 parts of polycarboxylic acid-based high-efficiency water reducer.
[0056] In the preparation method, the carboxyl functionalized carbon nanotube dispersion obtained in Preparation Example 1 is added in step S4 instead of the modified aggregate.
[0057] The difference from Example 1 is that no aggregate is added in this comparative example.
[0058] Comparative Example 3 A carbon nanotube-modified aggregate-containing UHPC is prepared from raw materials including the following components in parts by weight: 1467 parts of 52.5 grade ordinary Portland cement, 147 parts of incompletely densified silica fume, 4.22 parts of carboxyl functionalized carbon nanotubes, 39 parts of copper-plated straight steel fibers, 760 parts of sintered bauxite aggregate, 452 parts of tap water, and 5 parts of polycarboxylic acid-based high-efficiency water reducing agent; wherein the aggregate has not been modified.
[0059] The preparation method comprises: preparing cement, silica fume, steel fiber, aggregate, carboxyl functionalized carbon nanotubes, water and water reducing agent in proportion by weight; preparing carboxyl functionalized carbon nanotube dispersion; mixing dry powder materials such as cement, silica fume, steel fiber and unmodified aggregate, stirring evenly to obtain a dry mixture; then adding water, water reducing agent and carboxyl functionalized carbon nanotube dispersion to the dry mixture, stirring fully with a high-speed mixer until the mixture reaches a uniform state; appropriately pressing or casting the mixture, and curing and curing the mixture to obtain UHPC based on carboxyl functionalized carbon nanotube modified aggregate.
[0060] The difference from Example 1 is that although the raw materials include carboxyl functionalized carbon nanotubes, they are not used for aggregate modification but are directly added to the cementitious material.
[0061] Performance Testing Conventional mechanical tests and high-speed projectile penetration resistance tests were performed on the ultra-high performance concrete of the above-mentioned embodiments and comparative examples, and the results are shown in Table 1. The high-speed projectile penetration resistance test process is the same as that of the Chinese patent application with application number 2023117815297 (a kind of anti-penetration ultra-high performance concrete and preparation method and application), but the target speed is increased from 400 m / s to 650 m / s.
[0062] Table 1 Results of conventional mechanical tests and anti-high-speed projectile penetration performance tests
[0063] By comparing Table 1, it can be found that the compressive strength, elastic modulus and flexural strength of the examples are improved to varying degrees compared with those of comparative example 1. As the content of carbon nanotubes increases, the static mechanical properties are enhanced. Figure 3 As shown, the carbon nanotube dosage on the horizontal axis refers to the mass ratio of the carboxyl functionalized carbon nanotubes to the UHPC specimen.
[0064] With the continuous increase of carbon nanotube content, the anti-penetration performance of ultra-high performance concrete has also been significantly improved. Figure 4 As shown, the carbon nanotube dosage on the horizontal axis refers to the mass ratio of the carboxyl functionalized carbon nanotubes to the UHPC specimen.
[0065] According to the data in Table 1, we can obtain Figure 3 The relationship between the static mechanical properties of concrete materials and the amount of carbon nanotubes is shown in the figure, and Figure 4 The graph showing the relationship between the anti-penetration performance of the concrete material and the amount of carbon nanotubes added shows that the addition of modified aggregates and the effect of carboxyl-functionalized carbon nanotubes synergistically enhance the overall performance of the concrete.
[0066] The modified aggregate plays a positive role in the microstructure by interacting with carboxyl-functionalized carbon nanotubes. After the surface of the modified aggregate is functionalized by carbon nanotubes, it can better combine with the CSH gel in the cement matrix, promote the hydration reaction of the cement matrix and form a denser structure. The carbon nanotubes not only fill the tiny gaps between the aggregate and the cement matrix, but also strengthen the interface between the aggregate and the cement matrix through their unique nanoscale and aspect ratio characteristics, forming a bridging structure that can effectively withstand external loads.
[0067] Specifically, after adding carbon nanotubes to the modified aggregate, the physical and chemical effects between the aggregate surface and the carbon nanotubes are enhanced, making the bond between the cement matrix and the aggregate stronger. This modification improves the bonding force of the aggregate in the concrete and enhances the overall compressive and flexural properties of the concrete. When the concrete is subjected to external loads, the synergistic effect between the carbon nanotubes and the modified aggregate enhances the stress distribution efficiency, reduces the expansion and propagation of cracks, and thus improves the toughness and crack resistance of the concrete.
[0068] In addition, the presence of modified aggregates also improves the penetration resistance of concrete. Due to the effect of carbon nanotubes, the modified aggregates are more closely bonded to the cement matrix. When impacted or penetrated, the modified aggregates help disperse and transfer external loads, reducing stress concentration. This mechanism not only reduces the crack formation of concrete, but also effectively reduces the damage caused by impact and penetration, and improves the impact and penetration resistance of concrete. Especially in the high-speed projectile penetration test, the synergistic effect of modified aggregates and carbon nanotubes reduces crack propagation and the damaged area of the concrete surface, thereby enhancing the penetration resistance of concrete.
[0069] In summary, the addition of modified aggregate enables the aggregate and carbon nanotubes in the cement matrix to play a better synergistic role. The modified aggregate not only improves the mechanical properties of concrete, but also significantly improves the anti-penetration performance of concrete by enhancing the density of the material and reducing crack propagation. Compared with Comparative Example 1, the ultra-high performance concrete containing carboxyl functionalized carbon nanotubes and modified aggregates exhibits more superior comprehensive performance, which fully demonstrates the important role of carbon nanotube modified aggregates in ultra-high performance concrete.
[0070] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A UHPC based on carbon nanotube modified aggregate, characterized in that: The invention is prepared from raw materials including the following components in parts by weight: 517-617 parts of cement, 135-165 parts of silica fume, 35-43 parts of steel fiber, 800-1000 parts of sintered bauxite aggregate, 4.22-10.56 parts of carboxyl functionalized carbon nanotubes, 410-510 parts of water and 6-12 parts of water reducing agent; wherein the sintered bauxite aggregate is modified by carboxyl functionalized carbon nanotubes.
2. The UHPC based on carbon nanotube modified aggregate according to claim 1, characterized in that: The cement is 52.5 grade or 52.5R grade silicate cement or ordinary silicate cement.
3. The UHPC based on carbon nanotube modified aggregate according to claim 1, characterized in that: The amorphous silicon dioxide content in the silica ash is greater than 95 wt % and the specific surface area is greater than 21.0 m 2 / g.
4. The UHPC based on carbon nanotube modified aggregate according to claim 1, characterized in that: The steel fibers are copper-plated straight steel fibers with an average length of 13 mm and an average diameter of 0.16 mm.
5. The UHPC based on carbon nanotube modified aggregate according to claim 1, characterized in that: The maximum particle size of sintered bauxite aggregate is 10mm.
6. The UHPC based on carbon nanotube modified aggregate according to claim 1, characterized in that: The carboxyl functionalized carbon nanotubes are one or more of multi-walled carboxyl functionalized carbon nanotubes and single-walled carboxyl functionalized carbon nanotubes.
7. A method for preparing UHPC based on carbon nanotube modified aggregate according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1, preparing a carboxyl functionalized carbon nanotube dispersion and modifying sintered bauxite aggregate; S2, after mixing cement and silica fume, adding water reducer and water and continuing to mix and stir to obtain a first mixture; S3, mixing the first mixture with steel fibers to obtain a second mixture; S4. Adding the modified sintered bauxite aggregate to the second mixture, mixing and stirring to obtain the UHPC based on the carboxyl functionalized carbon nanotube modified aggregate.
8. The method for preparing UHPC based on carbon nanotube modified aggregate according to claim 7, characterized in that: In S1, the aggregate modification method is a physical adsorption method or a chemical modification method.
9. The method for preparing UHPC based on carbon nanotube modified aggregate according to claim 8, characterized in that: The method comprises step S5, casting and curing to a specified age.
10. An application of UHPC based on carbon nanotube modified aggregate according to any one of claims 1 to 6, characterized in that: Including applications in protective engineering.
Citation Information
Patent Citations
High-strength concrete composite material as well as preparation method and application thereof
CN102050603A
Nano-material composite concrete with super high performance
CN102199021A
Cited By
Special aggregate for high-strength UHPC (Ultra High Performance Concrete) as well as preparation method and application of special aggregate
CN120423803A
A high-strength UHPC special aggregate and its preparation method and application
CN120423803B